Glutathione S-transferase variants and hypertension. - Delles, C; Padmanabhan, S; Lee, W; Miller, W; McBride, M; McClure, J; Brain, N; Wallace, C; Marçano, A; Schmieder, R; Brown, M; Caulfield, M; et al. (2008)
OBJECTIVES: Glutathione S-transferases are involved in defences against oxidative stress. We have recently demonstrated reduced expression of glutathione S-transferase mu type 1 (Gstm1) in a rat model of hypertension. Here, we examine the association between GSTM variants and hypertension in human. METHODS: We screened 83 patients with hypertension and 46 controls for single nucleotide polymorphisms in GSTM genes by TaqMan single nucleotide polymorphism genotyping assays and DNA sequencing. We then genotyped 753 trios from the Medical Research Council British Genetics of Hypertension Study transmission disequilibrium test cohort for 10 single nucleotide polymorphisms and the GSTM1 deletion and examined renal GSTM expression in a cohort of 27 hypertensive and 18 normotensive subjects. Finally, we attempted to replicate our findings in 1675 cases and 1654 controls from the Medical Research Council British Genetics of Hypertension Study case-control cohort. RESULTS: We identified two major linkage disequilibrium blocks including GSTM4/GSTM2 and GSTM5/GSTM3 separated by the GSTM1 gene. In the British Genetics of Hypertension transmission disequilibrium test resource, a single nucleotide polymorphism in the 3' region of GSTM5 (rs11807) was found to be associated with hypertension (P = 0.01) with the T-allele being over-transmitted to hypertensive offspring. GSTM5 mRNA expression was found to be reduced in kidney tissue of subjects homozygous for the T-allele of rs11807 as compared to C-allele homozygous and CT heterozygous subjects (P = 0.02). Nevertheless, rs11807 was not associated with hypertension in the British Genetics of Hypertension case-control cohort (P = 0.61). CONCLUSION: Our studies do not provide an evidence of an association of GSTM gene variants with hypertension in humans. They, however, illustrate the essential role of replication of initial results in a second cohort.